2016
DOI: 10.5195/cajgh.2016.227
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs2294008 and rs9297976 Polymorphisms in PSCA Gene with Gastric Cancer Susceptibility in Uzbekistan

Abstract: Introduction:Genetic factors play an important role in the development of gastric cancer (GC), a prevalent malignancy in Central Asia. Recent studies have shown that single-nucleotide polymorphisms (SNPs) in several genes are associated with increased GC risk, indicating that genetic variation contributes to gastric carcinogenesis. Located on chromosome 8q24.2, the prostate stem cell antigen (PSCA) gene encodes a 123-amino acid glycoprotein related to the cell-proliferation inhibition and cell-death induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The study analyzed 925 DGC cases with 1396 controls and reported a strong association with the T allele at rs2294008 in PSCA . This association has also been observed in other populations across the world including Koreans [ 7 , 8 ], Uzbekistanis [ 9 ], and even Caucasians [ 10 , 11 , 12 ].…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…The study analyzed 925 DGC cases with 1396 controls and reported a strong association with the T allele at rs2294008 in PSCA . This association has also been observed in other populations across the world including Koreans [ 7 , 8 ], Uzbekistanis [ 9 ], and even Caucasians [ 10 , 11 , 12 ].…”
Section: Introductionsupporting
confidence: 66%
“…The study analyzed 925 DGC cases with 1396 controls and reported a strong association with the T allele at rs2294008 in PSCA. This association has also been observed in other populations across the world including Koreans [7,8], Uzbekistanis [9], and even Caucasians [10][11][12]. rs2294008 is located in the upstream region of PSCA, and a T to C transition at this single nucleotide polymorphism (SNP) causes a missense mutation (ATG to ACG) at the presumed translation-initiating codon in the first exon, resulting in a nine-amino-acid truncation of its signal peptide.…”
Section: Introductionmentioning
confidence: 68%
“…In Asia, the prevalence of Helicobacter pylori ( H. pylori ) is found as an important etiological factor for the development of gastric cancer [4]. In addition, previous studies showed that the potential environmental factors associated with gastric cancer might include tobacco smoking, alcohol use, dietary habits, unrefined vegetable oil, intake of water and daily consumption of meat-broth [5,6]. Furthermore, genetic factors have been also found to play an important role in the development of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, CA haplotype between rs2294008C/T and rs2976392A/G is associated with a significant reduction in gastric cancer in Tebyan population [ 86 ]. The role of rs2294008 and rs2976392 in the incidence of cancer in Uzbekistan has also been investigated and the results indicate that the rs2294008 T allele is associated with an increased risk of GC and rs2976392 located in intron 2 has a significant association with GC in women under 40 years of age [ 87 ].…”
Section: Psca Expression and Polymorphisms In Different Cancersmentioning
confidence: 99%